2012
DOI: 10.1073/pnas.1218667110
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C ameliorates diabetic nephropathy by epigenetically inhibiting the redox enzyme p66 Shc

Abstract: The coagulation protease activated protein C (aPC) confers cytoprotective effects in various in vitro and in vivo disease models, including diabetic nephropathy. The nephroprotective effect may be related to antioxidant effects of aPC. However, the mechanism through which aPC may convey these antioxidant effects and the functional relevance of these properties remain unknown. Here, we show that endogenous and exogenous aPC prevents glomerular accumulation of oxidative stress markers and of the redox-regulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
179
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(186 citation statements)
references
References 32 publications
7
179
0
Order By: Relevance
“…This is consistent with the findings of Bock et al, who found that glucose impaired the MMP and increased ROS levels (31). However, in the present study, SIRT4 overexpression increased the MMP and reduced ROS levels in podocytes under hyperglycemic conditions, indicating that SIRT4 overexpression inhibits apoptosis by reducing the generation of ROS from mitochondrial sources in podocytes.…”
supporting
confidence: 94%
“…This is consistent with the findings of Bock et al, who found that glucose impaired the MMP and increased ROS levels (31). However, in the present study, SIRT4 overexpression increased the MMP and reduced ROS levels in podocytes under hyperglycemic conditions, indicating that SIRT4 overexpression inhibits apoptosis by reducing the generation of ROS from mitochondrial sources in podocytes.…”
supporting
confidence: 94%
“…Several studies demonstrated a role of aPC in modulating mRNA expression by regulating transcription factor activity, mRNA stability, or through epigenetic mechanisms. 7,34,35 Within this study we establish that aPC additionally modulates protein stability via the ubiquitin-proteasome system. We show that aPC maintains the 50 kD form of full length YB-1 protein by decreasing the K48-linked YB-1 ubiquitination through an OTUB1-dependent mechanism.…”
Section: Discussionmentioning
confidence: 68%
“…5 Unlike thrombin, the anticoagulant serine protease activated protein C (aPC) is nephroprotective, ameliorating chronic 6,7 and acute 8,9 renal injury. The opposing effects of thrombin and aPC are largely controlled by thrombomodulin (TM).…”
mentioning
confidence: 99%
“…Low concentrations of thrombin are protective, whereas high concentrations lead to cell death in high-glucose culture. In many disease models, such as diabetic nephropathy, ischemia-reperfusion, and acute tubular injury, aPC signaling via EPCR and PAR1 reportedly restores renal function, protecting glomerular endothelial cells and renal tubular cells [55][56][57].…”
Section: Othersmentioning
confidence: 99%